2016
DOI: 10.1186/s12882-016-0387-3
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan metabolism, its relation to inflammation and stress markers and association with psychological and cognitive functioning: Tasmanian Chronic Kidney Disease pilot study

Abstract: BackgroundAdults with chronic kidney disease (CKD) exhibit alterations in tryptophan metabolism, mainly via the kynurenine pathway, due to higher enzymatic activity induced mainly by inflammation. Indoles produced by gut-microflora are another group of tryptophan metabolites related to inflammation and conditions accompanying CKD. Disruptions in tryptophan metabolism have been associated with various neurological and psychological disorders. A high proportion of CKD patients self-report symptoms of depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 69 publications
4
65
0
1
Order By: Relevance
“…Plasma concentrations of the PBUTs measured in our study population were higher than in the healthy population as reported in the literature, especially for the strongly protein bound toxins (Table 6) (kynurenine: 2.0-fold [23][24][25], kynurenic acid: 75-fold [26,27], indoxyl sulfate: 72-fold [28,29], indole-3-acetic acid: 2.4-fold [29], p-cresyl sulfate: 59-fold [29], p-cresyl glucuronide: 1.6-fold [30], and hippuric acid: 11-fold higher) due to impaired tubular secretion and limited removal during HD, since only the free fraction is available for diffusion across the dialysis membrane. Kynurenic acid, indoxyl sulfate, indole-3-acetic acid, p-cresyl glucuronide and hippuric acid concentrations were inversely related to renal creatinine clearance.…”
Section: Discussionsupporting
confidence: 54%
“…Plasma concentrations of the PBUTs measured in our study population were higher than in the healthy population as reported in the literature, especially for the strongly protein bound toxins (Table 6) (kynurenine: 2.0-fold [23][24][25], kynurenic acid: 75-fold [26,27], indoxyl sulfate: 72-fold [28,29], indole-3-acetic acid: 2.4-fold [29], p-cresyl sulfate: 59-fold [29], p-cresyl glucuronide: 1.6-fold [30], and hippuric acid: 11-fold higher) due to impaired tubular secretion and limited removal during HD, since only the free fraction is available for diffusion across the dialysis membrane. Kynurenic acid, indoxyl sulfate, indole-3-acetic acid, p-cresyl glucuronide and hippuric acid concentrations were inversely related to renal creatinine clearance.…”
Section: Discussionsupporting
confidence: 54%
“…To our knowledge, no other studies have quantified IAA levels in ADHD children. Urine IAA levels were correlated with anxiety and depression scores in adults with chronic kidney disease (Karu et al 2016). Moreover, no change is detected in urinary excretion of IAA in patients with depression, with slight increase only in cerebrospinal fluid levels in patients with depression and intellectual disability (Anderson et al 1984).…”
Section: Indole Responses To Methylphenidate 183mentioning
confidence: 99%
“…A previous study indicated that knocking out the Kynurenine formamidase gene, which is related to tryptophan degradation, in mice results in hardening of the glomerulus and an abnormal immune system . In addition, Karu et al reported that tryptophan metabolites may be decreased or elevated in CKD . Thus, it was speculated that the decline of these proteins would result in a lack of tryptophan, in turn causing abnormalities of the kidney.…”
Section: Amino Acid Metabolismmentioning
confidence: 99%
“…49 In addition, Karu et al reported that tryptophan metabolites may be decreased or elevated in CKD. 50 Thus, it was speculated that the decline of these proteins would result in a lack of tryptophan, in turn causing abnormalities of the kidney.…”
Section: Tryptophan Metabolismmentioning
confidence: 99%